2016
DOI: 10.1007/s11274-016-2126-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition in a strain of Bacillus subtilis, a producer of iturin A lipopeptides that are active against uropathogenic bacteria

Abstract: Urinary tract infections are a common disease in humans. Therefore, new methods are needed to destroy biofilms that are formed by uropathogens. Iturin A lipopeptides (LPs) C14 and C15 are potent biosurfactants synthetized by the Bacillus subtilis I 0 1a strain. The biological activity of extracted LPs was confirmed by examining extracts from I 0 1a cultures against uropathogenic bacteria that had been isolated from biofilms on urinary catheters. Compared with cultures of DSM 3257, which produce surfactin at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 44 publications
5
37
0
1
Order By: Relevance
“…Indeed, the first cluster of peaks near 1000 m/z are attributed to the lipopeptide homologues of surfactins and iturin family, while the second cluster of peaks near 1400 m/z is attributed to the lipopeptide homologues of fengycin family. In agreement with the result of this study, previous investigations reported that these nonribosomally synthesized CLPs produced by Bacillus have been found to be active against a wide range of phytopathogens (Roongsawang et al 2002;Ongena and Jacques 2008;Arguelles-Arias et al 2009;Zeriouh et al 2011;Hoefler et al 2012;Baindara et al 2013;Guo et al 2014;Bernat et al 2016;Paraszkiewicz et al 2017;Sarwar et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the first cluster of peaks near 1000 m/z are attributed to the lipopeptide homologues of surfactins and iturin family, while the second cluster of peaks near 1400 m/z is attributed to the lipopeptide homologues of fengycin family. In agreement with the result of this study, previous investigations reported that these nonribosomally synthesized CLPs produced by Bacillus have been found to be active against a wide range of phytopathogens (Roongsawang et al 2002;Ongena and Jacques 2008;Arguelles-Arias et al 2009;Zeriouh et al 2011;Hoefler et al 2012;Baindara et al 2013;Guo et al 2014;Bernat et al 2016;Paraszkiewicz et al 2017;Sarwar et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…LP biosurfactants greatly reduce surface and interfacial tension and they are known as good emulsifiers, dispersing and foaming agents used in chemistry, food production, agriculture, cosmetics and in environmental biotechnology for soil and water treatment. One of the tested strain, B. subtilis I'1a synthetized iturin A C14 and C15, which antimicrobial effects on planktonic and sessile form were confirmed for Escherichia coli, Serratia marcescens, Enterobacter cloacae, Proteus mirabilis, Citrobacter freundii and Enterococcus faecalis [4]. During the time of the experiment the changes in surface tension were also measured.…”
Section: Resultsmentioning
confidence: 94%
“…The concentration of formazan produced by T-1 strain was estimated about 0.0015 mg/ml. Abilities of LPs produced by bacilli to affecting the bacterial adhesion properties, flagella development or to disturb the integrity of membranes and inhibition of biofilm formation is well documented [4]. The negative influence of mixture consist of fengycin and surfactin produced by B. subtilis and B. licheniformis on E. coli and S. aureus adhesion was observed by Rivardo et al [23].…”
Section: Eko-dok 2017mentioning
confidence: 95%
See 2 more Smart Citations